ISLAM DAN PLURALISME - Anwira Nazifa; Ashri Hikmayanti Fatimah; Ayu Lestari; Destia Anjani (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The contemporary issue is a study which in which includes the discussion of the issues there is amid this modern era. The contemporary issue taken in this study is about Islam and pluralism. The discussion in it covers contemporary issues or issues presented with exposure and perspectives from a thematic exegesis study. The aim of the study is to examine contemporary questions of Islam and pluralism from the exegesis of the qur 'an. The discussion includes a study of the meaning of the prularism itself as well as the exegesis of the Mufasir of both previous old Mufasir and contemporary Mufasir. The method used in this research is by searching for meaning and literature, which is then used as a material or reference material in this study. The study of Islam and this pluralism produces that the meaning of this pluralism is a diversity of which diversity in the Qur'an itself has been much explaining about religious religion, including the letter al-Baqarah verse 62 and verse 256. This research is very useful to facilitate the means of teaching and learning activities and the results of the sourced study sourcing for those who need it.